Analisis Hubungan Tengkulak dan Petani dalam Kegiatan Jual Beli Padi di Desa Mayang, Kabupaten Jember - Ananda Ines Putri Winanti; Nur Intan Mutiara; Nadia Ulva Febrianti (Institut Nalanda, 2024)
The relationship between farmers and middlemen is an attachment to improve the economy and social networks. More narrowly, this attachment also extends to the personal relationship between the two. It even triggers the emergence of concern and trust. However, in this case, attachment is divided into Strong Ties and Weak Ties. Strong ties can be seen from the relationship between middlemen and farmers which is formed because of complementary needs. Meanwhile, weak ties can be seen when the relationship between middlemen and farmers is not going well. This research uses the perspective of attachment theory proposed by Granovetter. According to Granovetter, in every economic action there is an element of social action that is (embedded) in the intrapersonal social network between individuals and other individuals. The aim of the research is to find out how embeddedness occurs in the relationship that exists between farmers and middlemen. This type of research is qualitative with a phenomenological approach. The research results show that the attachment of farmers and middlemen is based on two different things, namely trust and personal interests.